Dengue virus infection – a review of pathogenesis, vaccines, diagnosis and therapy - Kok, Boon Hui; Lim, Hui Ting; Lim, Chin Peng; Lai, Ngit Shin; Leow, Chiuan Yee; Leow, Chiuan Herng (Virus research, 2023)
•Reviews on unsolved issues of DENV from different perspectives such as the effect of antibody dependent enhancement, immune escape and limitations of commercial diagnostic kits.•Case studies on variety of potential therapeutic candidates targeting on DENV such as peptide inhibitors, broadly neutralizing antibodies, engineered antibody, vaccine candidates and antiviral agents.•Exploring different approaches for the improvisation of DENV diagnosis such as application of bio-functionalized tapered optical fiber, nanobody derivatives and antibody engineering. The transmission of dengue virus (DENV) from an infected Aedes mosquito to a human, causes illness ranging from mild dengue fever to fatal dengue shock syndrome. The similar conserved structure and sequence among distinct DENV serotypes or different flaviviruses has resulted in the occurrence of cross reaction followed by antibody-dependent enhancement (ADE). Thus far, the vaccine which can provide effective protection against infection by different DENV serotypes remains the biggest hurdle to overcome. Therefore, deep investigation is crucial for the potent and effective therapeutic drugs development. In addition, the cross-reactivity of flaviviruses that leads to false diagnosis in clinical settings could result to delay proper intervention management. Thus, the accurate diagnostic with high specificity and sensitivity is highly required to provide prompt diagnosis in respect to render early treatment for DENV infected individuals. In this review, the recent development of neutralizing antibodies, antiviral agents, and vaccine candidates in therapeutic platform for DENV infection will be discussed. Moreover, the discovery of antigenic cryptic epitopes, principle of molecular mimicry, and application of single-chain or single-domain antibodies towards DENV will also be presented.